Turkish History and Culture in India
1 online resource.
Keywords: This interdisciplinary volume addresses the history, literature and material culture of peoples of Turkish origins in India over the eleventh to eighteenth centuries. Although many ruling dynasties and members of the elite in this period claimed Turkish descent, this aspect of their identity has seldom received much scholarly attention. The discussion is enriched by a focus on connections and comparisons with other parts of the broader Turko-Persian world, especially Anatolia. Although discussions of Turkish-Muslim rulers in India take account of their Central Asian origins and connections, links with Anatolia, stretching back to the medieval period, were also important in the formation of Turkish society and culture in India, and have been much less explored in the literature. The volume contains contributions by some of the leading scholars in the field.